PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA CAFE KOPI TUH DI KABUPATEN TANGERANG - Aqil, Muhammad; Haryantini (Journal of Research and Publication Innovation, 2024)
This thesis uses quantitative research that aims to determine how much influence product quality and price have on consumer satisfaction at Tuh Coffee Cafe, Tangerang Regency. The population in this study was consumers at Cafe Kopi Tuh Tangerang Regency which amounted to 22,539 people and a sample of 100 people, the sample technique used was the slovin sample technique, the data collection technique used in this study was the observation method and questionnaire. The purpose of this study is to determine the Effect of Product Quality and Price on Consumer Satisfaction of Tuh Coffee Cafe, Tangerang Regency, product quality (X1) has a significant effect on consumer satisfaction (Y). Test the hypothesis obtained Tcalculate > Ttabel or (3.227 > 1.661) with a significant value of 0.002 < 0.05, it can be concluded that H0 is rejected and H1 is accepted. This means that there is an influence of product quality on consumer satisfaction at Caffe Kopi Tuh, Tangerang Regency. Price (X2) has a significant effect on purchasing decisions (Y). Test the hypothesis obtained Tcalculate > Ttabel or (2.067 > 1.661) with a significant value of 0.041 < 0.05 then it can be concluded that H0 rejected H2 is accepted. This means that there is an effect of price on consumer satisfaction at Cafe Kopi Tuh, Tangerang Regency. The hypothesis test was obtained by Fcalculate > Ftabel or (60.497> 2.36) with a significant value of 0.002 < 0.05. Thus H0 is rejected and H3 is accepted. This means that there is a simultaneous positive and significant influence between Product Quality and Price on Consumer Satisfaction at Tuh Coffee Cafe, Tangerang Regency. The value of the Coefficient of Determination or R Square (R2) is 0.555 or equal to 55.55% which shows that the product quality variable (X1) and the price variable (X2) simultaneously (together) affect the consumer satisfaction variable (Y) by 55.5% while 44.5% is influenced by other variables that are not studied.